2010
DOI: 10.1007/s11255-010-9735-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study to evaluate the effect of double dartos flaps in primary hypospadias repair: no fistula anymore

Abstract: The additional covering of the neourethra with a second layer dartos flap is an improvement in the TIP urethroplasty, in terms of fistula formation avoidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…21Y24 Other authors have recently reported the effectiveness of a double protection layer of the dartos fascia, who compared this method with flapless TIPU, TIPU protected by a single dartos flap. 10 Although this work has excellent results in the double dartos group with only 0.7% fistula rate, however, it is very noticeable that this group alone consisted of more than 76% of the study population. The small numbers of the other groups invalidated the W 2 approximation and the likelihood quotient was used which is questionable in validity and reliability.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…21Y24 Other authors have recently reported the effectiveness of a double protection layer of the dartos fascia, who compared this method with flapless TIPU, TIPU protected by a single dartos flap. 10 Although this work has excellent results in the double dartos group with only 0.7% fistula rate, however, it is very noticeable that this group alone consisted of more than 76% of the study population. The small numbers of the other groups invalidated the W 2 approximation and the likelihood quotient was used which is questionable in validity and reliability.…”
Section: Discussionmentioning
confidence: 62%
“…8,9 The etiology of fistula has been a controversial issue in pediatric urology and several factors such as suture material, infection, previous operations, catheterization, and surgical skill may affect outcomes significantly. 10 One of the most important techniques to avoid in the occurrence of fistulas is the application of a protective vascularized intermediate layer between the neourethra and the skin such as the external spermatic fascia, spongial tissue, tunica virginals, and scrotal, dorsal, and ventral dartos flaps. 11Y14 However, there is no general consensus about the best interpositional flap coverage to decrease the fistula rate which perhaps is caused by the associated potential harvesting complications, individualized level of surgeon's experience, different complexity degrees of different repairs, using different surgical materials including sutures and catheters, and the bias of applying a specific technique for many forms of the anomaly itself.…”
mentioning
confidence: 99%
“…[3,7,10] Recently, in a study done by Yigiter et al, the authors compared the complication rates of the flapless, single flap, double flaps and procedures in TIPU, and reported a 29.4%, 26% and 0.1% incidence of fistulas, respectively. [20] In our previous studies, we concluded that TIPU with double dartos flaps seems far more effective in completely covering the neourethra than the methods including a single flap. [13,14] The reason for fistula development is not well known in single dartos flaps covering the neourethra.…”
Section: Discussionmentioning
confidence: 89%
“…A ventrally based dartos flap was also used to reduce fistula formation 12 .Furthermore, reports of having used dorsal double dartos flaps have proven to be more superior than single rotational dorsal dartos flap with the least complications of fistulae and penile torsion 3,5 .…”
Section: Discussionmentioning
confidence: 99%
“…The procedure is easy to follow and gives good cosmetic and functional results 1 . Despite its versatility and the obvious surgical advances that it represents in hypospadias repair, urethrocutaneous fistula is the most common complication of TIP, the reported incidence being as high as 13% --29.4% 2,3 . The incidence of which has been used to evaluate the success of hypospadias repair.…”
Section: Introductionmentioning
confidence: 99%